2020
DOI: 10.1098/rsos.191595
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and molecular docking studies reveal binding characteristics of nazartinib (EGF816) to human serum albumin

Abstract: The interactions of novel anti-cancer therapeutic agents with the different plasma and tissue components, specifically serum albumins, have lately gained considerable attention due to the significant influence of such interactions on the pharmacokinetics and/or -dynamics of this important class of therapeutics. Nazartinib (EGF 816; NAZ) is a new anti-cancer candidate proposed as a third-generation epidermal growth factor receptor tyrosine kinase inhibitor that is being developed and clinically tested for the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“… a Thermodynamic parameters of the protein–drug binding. b Ref . c Ref . d Ref . e Ref . f Ref . g Ref . h Ref . i Ref . j Ref . k Ref . l Ref …”
Section: Resultsmentioning
confidence: 99%
“… a Thermodynamic parameters of the protein–drug binding. b Ref . c Ref . d Ref . e Ref . f Ref . g Ref . h Ref . i Ref . j Ref . k Ref . l Ref …”
Section: Resultsmentioning
confidence: 99%
“…UV-VIS absorption spectroscopy is a basic spectrometric method used to investigate structural changes that accompany the formation of bound ligand–protein complexes [ 27 , 28 ]. The aromatic amino acids in proteins, tryptophan and tyrosine, strongly contribute to UV absorption of proteins at 280 nm and 274 nm respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It could be suggested that the spontaneous interaction between HSA and 4-HBA or VA had occurred in the systems. The negative value of ΔH and ΔS represented the hydrogen bonding and Van der Waals forces [ 28 , 29 ]. The results in Table 3 showed that the ΔH and ΔS values also were negative values in HSA-4-HBA and HSA-VA system, indicating that hydrogen bonds and Van der Waals forces contributed in the binding of HSA to 4-HBA or VA.…”
Section: Discussionmentioning
confidence: 99%